The effect of a varied recreational kinetic program accompanying music in Anxiety level and some body measurements for women (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare a diverse recreational movement program accompanying music in the level of anxiety and some physical measurements for women, and the researcher hypothesised that there are statistically significant differences between the results of the pre-tests and the results of the post-tests for some psychological variables for the experimental and control groups in the research sample.The second chapter also contained theoretical and similar studies that revolved around several axes, including: the psychological program, the kinetic program, recreation, the musical rhythm, anxiety and some physical measurements and similar studies. The third chapter included research procedures as the researcher used the experimental method on a sample of working women aged 35- 45 years, as the sample was randomly divided into two groups, an experimental group and a control group of (10) women for each group. A group after conducting an exploratory experiment, and the researcher processed the results of the pre and post tests using appropriate statistical means, for the purpose of arriving at accurate results. Then the search results were extracted by using the spss statistical system.